PENGARUH GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT, UKURAN PERUSAHAN DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK: (Studi Empiris Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Ganda Siahaan (Amal Insani Foundation, 2020)
This study aims to determine the effect of good corporate governance, audit quality, company size, and leverage on tax avoidance in Consumer Goods Companies Listed on the Indonesia Stock Exchange from 2012-2016. This research is designed using a quantitative approach and belongs to the type of explanatory research. The population to test the hypothesis of this study is all companies included in the Consumer Goods Sector listed on the Indonesia Stock Exchange for the period 2011 to 2016, totaling 34 companies. Meanwhile, the determination of samples in this study was carried out by purposive sampling and determined by 31 companies. The type of data in this study uses secondary data, the secondary data used is the financial statements of consumer goods companies for the period 2011-2016. Data collection techniques are carried out by observation and documentation of research samples. The data analysis method in this study used multiple regression. The results showed that institutional ownership did not have a significant negative influence on tax avoidance. An independent board of commissioners does not have a significant negative influence on tax evasion. Managerial ownership has a significant positive effect on tax evasion. The quality of the audit did not have a significant positive effect on tax evasion. Leverage has a significant negative effect on tax evasion. The size of the enterprise negatively affects tax avoidance.